Commensal bacteria aggravate allergic asthma via NLRP3/IL-1β signaling in post-weaning mice. (September 2018) - Huang, Chao; Wang, Jian; Zheng, Xiaodong; Chen, Yongyan; Zhou, Rongbin; Wei, Haiming; Sun, Rui; Tian, Zhigang
Abstract: Perturbation of commensal bacteria by antibiotic exposure aggravates ovalbumin (OVA)-induced allergic asthma in pre-weaning mice. However, the influence of dysbiosis of commensal bacteria on asthma development in post-weaning mice is still limited. Here, we treated 3-week-old post-weaning mice with antibiotics to disrupt commensal bacteria and then established OVA-induced allergic asthma by peritoneal sensitization using OVA/alum and intranasal challenge with OVA. Contrary to the protective function in pre-weaning mice, commensal bacteria in post-weaning mice aggravated OVA-induced asthma. Commensal bacteria in post-weaning mice promoted OVA-induced allergic asthma through maintenance of NLRP3/IL-1β expression in peritoneal macrophages (pMφ), which promoted recruitment of inflammatory cells, especially inflammatory monocytes, into the peritoneal cavity after OVA/alum sensitization. Further study showed that metronidazole- and vancomycin-sensitive bacteria are involved in maintenance of NLRP3/IL-1β signal in pMφ. Our results suggest that certain species of commensal bacteria in post-weaning mice aggravate OVA-induced allergic asthma through NLRP3/IL-1β signal pathway. Graphical abstract: Highlights: Contrary to the protective role in pre-weaning mice, commensal bacteria in post-weaning mice aggravate OVA-induced asthma. NLRP3/IL-1β signaling in peritoneal macrophages (pMφ) plays an essential role in OVA-induced allergic asthma. Commensal bacteria maintain NLRP3/IL-1β signaling in pMφ to promote inflammatory monocyte recruitment after sensitization. Metronidazole- and vancomycin-sensitive bacteria are major players in maintenance of NLRP3/IL-1β signal in pMφ.